2004
DOI: 10.1177/003368820403500106
|View full text |Cite
|
Sign up to set email alerts
|

Significant Motivational Predictors of the Amount of Reading By Efl Learners in Japan

Abstract: Although there is extensive research into what constitutes second language learning motivation and how it works, most of the existing work is carried out in ESL environments, and is mainly concerned with motivation to communicate using the target language. However, in EFL environments such as Japan, students have quite limited contact with target language communities, and consequently need to rely largely on written form of input. Thus, this study attempted to investigate the relationship between how students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…Several studies mentioned that integrative motivation was stronger than instrumental motivation based on Gardner's study. However, Mori (2004) indicated that the research showed that instrumental motivation was helpful to gain proficiency information, while integrative motivation was not. Schmidt, Boraie and Kassabgy's study indicated that the language Egyptian learners who used in the classroom learning environment could not be suitable for Gardner's Model.…”
Section: B Motivation In the Learning Processmentioning
confidence: 97%
“…Several studies mentioned that integrative motivation was stronger than instrumental motivation based on Gardner's study. However, Mori (2004) indicated that the research showed that instrumental motivation was helpful to gain proficiency information, while integrative motivation was not. Schmidt, Boraie and Kassabgy's study indicated that the language Egyptian learners who used in the classroom learning environment could not be suitable for Gardner's Model.…”
Section: B Motivation In the Learning Processmentioning
confidence: 97%
“…In the field of L2 reading research, ER researchers have also demonstrated that intrinsic motivation is a significant predictor of reading amount (Mori, 2002(Mori, , 2004Takase, 2007), revealing the importance of intrinsic motivation in ER. In terms of factors contributing to the enhancement of intrinsic motivation for ER, some researchers argue that ER itself cultivates positive attitudes and motivation for L2 reading (e.g., Fujita & Noro, 2009;Matsui & Noro, 2010;Yamashita, 2013).…”
Section: Reading Motivationmentioning
confidence: 99%
“…In fact, the negative finding on reading challenge could be argued to imply that students do not seem to be equipped with critical thinking skills that allow them to recognize, resolve, assess, and figure out the complexities that emerge in reading (Waters, 2006cited in Fahim & Barjasteh, 2012. Such a shortcoming might be due to in part to the use of grammar translation method as the basic approach and framework in the Iranian EAP classes (Erfani et al, 2010).This finding indicates the importance of intrinsically oriented constructs in explaining EAP readers" motivation as suggested in the literature (e.g., Alsheikh & Elhoweris, 2011;Blay, Mercado &Villacorta, 2009;Lin et al, 2012;Mori, 2002Mori, , 2004. Blay et al ISSN 1948-5425 2012 www.macrothink.org/ijl 382 (2009), for instance, examined the nature of Grade-4 Filipino students" motivation to read.…”
Section: Resultsmentioning
confidence: 97%
“…That is, they have a multifaceted motivation to read, as is the case in other EFL contexts (i.e. Alsheikh & Elhoweris, 2011;Han, 2011;Kim, 2011;Mori, 2002Mori, , 2004Nishino, 2005).The varying levels of English proficiency of the participants could be one of the reasons for the different degrees of motivation. For example, the findings indicate that extrinsic factors for English reading are the most powerful predictors of low achieving students" engagement in reading.…”
Section: Motivational Effect Of Grades On Self-efficacymentioning
confidence: 95%